Analysis of the Oil Market and the Role of Investment in the Agrarian Sector in Kazakhstan - Smagulova, Sholpan Ð.; Doskeyeva, Gulashar Zh.; Radko, Natalya (International Journal of Economics and Financial Issues, 2016)
The research study examines the economic development of the oil industry of Kazakhstan. It is noted that in view of the decline in world oil prices, the growth of the various methods of oil production, including shale technology - low income from its production dropped. Therefore, with a view to sustainable development and the maintenance of macroeconomic stability should strengthen the development of the agricultural sector. The agro-industrial sphere amid growing global consumer demand and prices is gaining momentum. The benefits of attracting investment in this area can be attributed - availability of a vast territory, favorable climatic conditions, a lot of experience in the production of agricultural crops. In conclusion, given the findings on the forecast of development of the oil market and recommendations for improving the flow of investments in the agricultural sector of the country. Keywords: oil industry in Kazakhstan, world oil prices, investments, agricultural sector JEL Classifications: Q1, Q2, Q3